A Highly Transparent Artificial Photonic Nociceptor. Issue 19 (29th March 2019) - Kumar, Mohit; Kim, Hong‐Sik; Kim, Joondong
Abstract: A nociceptor is an essential element in the human body, alerting us to potential damage from extremes in temperature, pressure, etc. Realizing nociceptive behavior in an electronics device remains a central issue for researchers, designing neuromorphic devices. This study proposes and demonstrates an all‐oxide‐based highly transparent ultraviolet‐triggered artificial nociceptor, which responds in a very similar way to the human eye. The device shows a high transmittance (>65%) and very low absorbance in the visible region. The current–voltage characteristics show loop opening, which is attributed to the charge trapping/detrapping. Further, the ultraviolet‐stimuli‐induced versatile criteria of a nociceptor such as a threshold, relaxation, allodynia, and hyperalgesia are demonstrated under self‐biased condition, providing an energy‐efficient approach for the neuromorphic device operation. The reported optically controlled features open a new avenue for the development of transparent optoelectronic nociceptors, artificial eyes, and memory storage applications. Abstract : An ultraviolet‐stimuli‐triggered artificial nociceptor is proposed and demonstrated using an all‐oxide‐based highly transparent memristor. The device functions in a very similar manner to the human eye, and it satisfies all nociceptive features, such as threshold, relaxation, allodynia, and hyperalgesia, depending on the stimulus strength, duration, and repetition rate under self‐biased conditions.